The Effectiveness Madrasa Cultural Facilities Regarding Learning Technology In Increasing The Competitiveness of Madrasas - Rochim, Fathur; Merita, Rona (Journal of Instructional and Development Researches, 2025)
Madrasah Culture is "a distinctive characteristic of a Madrasah that can be identified through the values it upholds, the attitudes it has, the habits it displays, and the actions shown by all Madrasah personnel who form a special unity of the Madrasah systemEducation is one of the important means in building a nation and state. Because through education will be formed human resources that are qualified. Moreover, today with the rapid development of science and technology, especially in the field of communication and electronics, resulting in an information revolution in all areas of life without recognizing geographical, political. However, research that focuses on Madrasah culture in increasing competitiveness in Madrasah is relatively rarely done. This study takes a broader focus, namely Madrasah facilities in increasing Madrasah competitiveness.The results of the study found that facilities are very vital in education because without facilities the teaching and learning process will be hampered, therefore in MAN 1 Jombang and MAN 4 Jombang, madrasah facilities are greatly improved. The madrasah facilities in MAN 1 and MAN 4 Jombang are: a). The creation of comfortable and safe madrasah community activities because of the madrasah facilities, so that it can increase the competitiveness of the madrasah. b). Providing comfort in the teaching and learning process with standard facilities c). The formation of a madrasah culture from the behavior of madrasah residents based on the madrasah culture progra d). Providing facilities and appropriate containers for madrasahs. e). Utilizing existing facilities and periodic repairs. f). Providing adequate facilities in its time. g). Madrasah facilities are very important because in improving the quality culture in both locations because the quality culture is created from adequate and good madrasah facilities h). and also the last research findings on madrasah facilities.